Managing subsystem interfaces of complex products. (19th January 2011) - Rahmani, Keyvan; Thomson, Vincent
An interface management model for multidisciplinary products is proposed with the aim of improving communication between design groups. The systematic methodology described in this paper captures the interaction of different systems in an object oriented model. This helps to define the connectivity of subsystems such that the effect of modifications is more visible to designers. With the use of common definitions and greater visibility of the impact of changes, the number of incompatible design decisions is reduced. This results in lower product development times and eases subsystem modifications. Interfaces are modelled using object oriented technology since this parallels the object nature of product data and since object technology provides a formalised way of integrating interfaces into product data management software.